Improvement of the system of indicators for the efficiency evaluation of the production capacity of industrial enterprises - Skrynkovskyy, Ruslan; Sopilnyk, Rostyslav; Seliverstova, Liudmyla; Koropetskyi, Oleh; Protsiuk, Tetiana (Technology audit and production reserves, 2018)
The object of research is the features of the formation, use and improvement of the system of indicators to assess the efficiency of the production potential of industrial enterprises. One of the main characteristics of the development of an industrial enterprise and the formation of its prospects, regardless of the goals set, is to ensure optimal competitiveness, stability, sustainable development, etc. – its potential, in particular production. It was found that the production potential is the existing and potential possibilities for the production of real output (in accordance with the needs of the market), the availability of production factors, the availability of basic types of resources. Here, analysis, systematization, synthesis and explanation of factors affecting the efficiency of the production potential of an industrial enterprise in the system to ensure its competitiveness are important. In the context of this, the graphical model of the interconnection of strategic plans and programs of industrial enterprises is improved. And also features, a role and a place of industrial enterprise production capacities in the hierarchy of factors (competitive forces) determining its competitiveness are taken into account. In the process of research, the methods of system analysis, systematization, generalization and methods of economic and mathematical modeling are used. According to the research results, it is established that for the effective use of the production potential of industrial enterprises it is necessary to ensure management on the basis of complete and objective information about the state of the components of the production potential by a system of relative indicators (coefficients). This system should correspond to the modern understanding of the essence of the concept of "efficiency", its types (financial and economic, industrial, commercial), strategic plans and programs, and strategies. The system of indicators is improved to assess the efficiency of the industrial potential of industrial enterprises, which takes into account the hierarchy of factors (competitive forces) determining its competitiveness, taking into account the main forces operating in the microenvironment of the enterprise. The presented studies should be taken into account when improving the fundamental (in-depth) system for diagnosing the production activities of industrial enterprises (as a partial diagnostic goal in the system of economic diagnostics goals).